The Analysis of Finance Division Employees’ Performance at North Sumatera’s DPRD Office - Dina Audiva Adawiyah (Indonesian Journal of Multidisciplinary Science, 2021)
The society of each country consists of various organizations that have the same goals and work together to achieve the goals. This study aims to determine the performance of employees in the finance departmentat the Medan City DPRD Secretariat office. Thisresearch is a qualitative approach and in descriptive form. Data collection techniques used are observation and interviews. This data collection tool uses interview guidelines, communicating directly. The researcher concludesthat the employees of the finance department both in the task of analyzing performance in the financial sector, employees and are responsible for work in each financial sector, employees provide examples to each other for other employees, employees have aspirit of leadership and responsibility in each field, and employees really miss service and implement the vision and mission at the Medan City DPRD Secretariat office.